Neonatal and pediatric pharmacology : therapeutic principles in practice - Yaffe, Sumner J; Aranda, Jacob V (Lippincott, Williams & Wilkins, 2005)
Written by experts at the forefront of current research and clinical practice, this volume provides evidence-based guidelines for safe, effective, and rational drug therapy in newborns, children, and adolescents. Coverage includes specific recommendations for all major drug classes and diseases, a detailed section on drugs and the newborn, and chapters on specific treatment settings such as the pediatric intensive care unit and emergency room. Also included are chapters on adverse effects and interactions and state-of-the-art discussions on pharmacokinetics, pharmacodynamics, pharmacogenetics, drug development, and clinical drug trials in infants and children. Appendices include a neonatal formulary and a pediatric formulary.
Keywords: nemoci novorozenců; Infant, Newborn, Diseases; perinatologie a neonatologie; farmakoterapie; Drug Therapy